FAKTOR YANG BERHUBUNGAN DENGAN PEMILIHAN KONTRASEPSI RASIONAL - Ayu Fitrianti; Ratna Dewi; Sri Yanniarti (Poltekkes Kemenkes Bengkulu, 2020)
Abstract: Based on the 2017 IDHS, contraceptive use in Indonesia is (64%) including modern contraceptive methods (57%) and traditional contraceptive methods (6%). The aim of this study was to find out the factors related to the selection of rational contraception in the Jalan Gedang Community Health Center Area. This type of research was analytical with a quantitative approach using a cross sectional design. Sampling was done by accidental sampling technique, which amounted to 91 where the sample in the study were all family planning acceptors in the Jalan Gedang Community Health Center in Bengkulu City.This study used Chi square statistical test with computerized system significance level p <0.05 where the results of the study stated that the variables related to the selection of rational contraception were knowledge p = 0.048 and acceptor attitudes p = 0.015, while unrelated variables were husband's support p = 0.981, the role of health workers p = 0.166, and information sources p = 0.078. The factor most associated with the choice of rational contraception is the attitude of the acceptor with the Exp value (B) = 4,275.Health services are expected to provide counseling and motivation especially the attitude of acceptors to the selection of contraception in order to build awareness that rational contraceptive choices are the right choice, and increase knowledge by disseminating information through counseling, so that knowledge of family planning acceptors can increase.Keywords: Rational, knowledge, husband's support, the role of health workers, acceptors' attitudes, information sources